The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/qj.551
|View full text |Cite
|
Sign up to set email alerts
|

The influence of rotational frontogenesis and its associated shearwise vertical motions on the development of an upper‐level front

Abstract: The total quasi-geostrophic (QG) vertical motion is partitioned into transverse and shearwise couplets oriented parallel to, and along, the geostrophic vertical shear, respectively, in order to examine the role of rotational frontogenesis, and its associated shearwise circulation, in the life cycle of an upper-front/jet system in northwesterly flow. In particular the analysis emphasizes two aspects of that role: (1) the influence of shearwise ω on scalar frontogenesis, and (2) the effect of rotational frontoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Recent studies that explore the role of latent heating during WCB ascent in creating midtropospheric positive PV anomalies and upper-tropospheric negative PV anomalies include Pomroy and Thorpe (2000), Knippertz and Wernli (2010), Lang (2011), Schemm et al (2013), and Madonna et al (2014). Cooper et al (2004) showed that penetration of stratospheric intrusions by convection can facilitate subsequent mixing into the troposphere.…”
Section: Convective Influences On Ste Near Jetsmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies that explore the role of latent heating during WCB ascent in creating midtropospheric positive PV anomalies and upper-tropospheric negative PV anomalies include Pomroy and Thorpe (2000), Knippertz and Wernli (2010), Lang (2011), Schemm et al (2013), and Madonna et al (2014). Cooper et al (2004) showed that penetration of stratospheric intrusions by convection can facilitate subsequent mixing into the troposphere.…”
Section: Convective Influences On Ste Near Jetsmentioning
confidence: 98%
“…Cold air advection along the UTLS jet axis has been shown to be compatible with sinking downstream of a trough at synoptic scales (Martin 2006;Lang and Martin 2010). Sawyer (1949) explored the possible role of inertial or symmetric instability in the UTLS in modifying midlatitude cyclogenesis, jet stream behavior, and meridional circulations.…”
Section: B Rwb Inertial Instability and Westerly Jetsmentioning
confidence: 98%
“…It is clear that the effective horizontal rotational frontogenesis (Figure 2a) is much smaller than that afforded by tilting (Figure 2b), suggesting a predominant role for tilting in changing the geostrophic temperature advection. Lang and Martin (2010) proposed a conceptual model, illustrated in their figure 13, which suggested that the development of along-flow geostrophic cold air advection was dependent on both kinematic rotation of ∇θ and alongflow tilting. Given the re-evaluation of the kinematics offered in this response, it is likely that rotation by deformation provides the kinematic contribution that we mistakenly attributed to the vorticity in our original paper.…”
Section: Rotation Of ∇φmentioning
confidence: 99%
“…The role of that vertical circulation in initiating geostrophic cold air advection along the flow is particularly at issue in Schultz (2012). Lang and Martin (2010) entered an ongoing debate between two competing hypotheses regarding the initiation of geostrophic cold air advection in the upper frontogenesis process and attempted to devise a more complete explanation that borrowed from both. Rotunno et al (1994, hereafter RSS94), using idealized baroclinic channel model simulations, examined the intensification of an upper-level front from a nearly equivalent barotropic initial state.…”
Section: Introductionmentioning
confidence: 99%
“…Sutcliffe, 1947;Trenberth, 1978), which exists along the jet axis when geostrophic cold air advection is present along an ULJF. Keyser and Pecnik (1987) showed that subsidence through the jet core is upper frontogenetic, thus the establishment of geostrophic cold air advection along the jet has been described as an important aspect of the upper front life cycle (Rotunno et al, 1994;Schultz and Doswell, 1999;Lang and Martin, 2010). An environment characterized by geostrophic warm air advection through the jet core shifts the thermally direct (indirect) circulation in the jet entrance (exit) region toward the cyclonic (anticyclonic) side, so that the jet core is conversely characterized by ascent (Figure 3(c)).…”
Section: Introductionmentioning
confidence: 99%